The Influence of the Implementation of the Watch Service on Security When Berthing at the Pier on the Training Ship John Lie - Wijaya, Haryadi; Setiawan, Hadi; Saifuddin, Iksan (Journal of Engineering and Transportation, 2024)
This research is based on an incident that occurred on March 4 2021 at exactly 08:20 LT (Local Time) when the ship was docked at the port of Merauke, Papua, a theft occurred which resulted in the paint being in the bosun store as well as personal belongings belongings of the ship's crew were lost stolen. So the author raises the problem of how the guard service is carried out when the ship is docked at the port with the aim of knowing the implementation of the guard service on the John Lie Training Ship when the ship is docked at the port. The method used in this research is a qualitative method which produces descriptive data in the form of written words from people and observed behavior. The data source used is primary data obtained directly from the research site by making observations, which are related to the title of the thesis. The results of research and discussion of problems in this thesis show that the implementation of guard duty on the John Lie Training Ship has not been carried out optimally. This was due to a lack of understanding of responsibilities while carrying out guard duties while docked at the port and a lack of communication between the officer on duty and the crew on duty.